2004
DOI: 10.1002/cncr.20617
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral prophylactic mastectomy

Abstract: BACKGROUND Women with unilateral breast carcinoma are at increased risk for developing contralateral breast carcinoma (CBC). The authors sought to identify predictors of malignant or moderate to high‐risk histologic findings in contralateral prophylactic mastectomy (CPM) specimens, and to determine the efficacy of CPM. METHODS The authors performed a retrospective review of 239 patients with unilateral early‐stage breast carcinoma who underwent CPM. The number of CBCs expected if the contralateral breast had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In considering the risk of the proposed surgery, one must also consider how the surgery will effect adjuvant therapy; even minor wound complications may potentially delay recommended chemotherapy or radiation therapy for the primary cancer after surgery. Indeed, in a previous study, we found that bilateral mastectomy for unilateral cancer conferred a higher risk of complications than unilateral mastectomy, with 8.4% of the complications occurring on the primary side, 6.3% occurring on the contralateral side, and 1.7% occurring bilaterally; thus, CPM does increase the complexity of the surgical procedure and may increase the complications incurred 1 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In considering the risk of the proposed surgery, one must also consider how the surgery will effect adjuvant therapy; even minor wound complications may potentially delay recommended chemotherapy or radiation therapy for the primary cancer after surgery. Indeed, in a previous study, we found that bilateral mastectomy for unilateral cancer conferred a higher risk of complications than unilateral mastectomy, with 8.4% of the complications occurring on the primary side, 6.3% occurring on the contralateral side, and 1.7% occurring bilaterally; thus, CPM does increase the complexity of the surgical procedure and may increase the complications incurred 1 .…”
Section: Discussionmentioning
confidence: 86%
“…Women diagnosed with breast cancer have a significantly increased lifetime risk of developing contralateral breast cancer (CBC) over the general population 14 . Gao et al evaluated the incidence of CBC in 134,501 patients previously diagnosed with breast cancer identified from the Surveillance, Epidemiology, and End Results (SEER) database and found that the actuarial incidence of CBC at 5, 10, 15, and 20 years was 3%, 6.1%, 9.1%, and 12%, respectively, or approximately 0.6% per year 5 .…”
Section: Introductionmentioning
confidence: 99%
“…9,7,21,23 In a prospective study, Meijers-Heijbor et al 20 evaluated the incidence of BC among 139 BRCA1 and BRCA2 mutation carriers who elected to undergo either BPM or close surveillance only. During an average follow-up interval of 3 years, 8 of the 63 women in the surveillance group developed BC, whereas none of the 76 women in the prophylactic-mastectomy group developed BC.…”
Section: Discussionmentioning
confidence: 99%
“…Goldflam and colleagues 23 found evidence that family history of BC was mostly associated with CPM. They retrospectively reviewed data for 239 patients with unilateral early-stage BC who elected to undergo CPM, and family history of BC was the most frequent reason given to undergo CPM in more than half of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…(18) Studies have shown that the complication rate associated with CPM is similar to the rate of complication for surgery on the side of the index breast cancer and thus CPM at time of therapeutic mastectomy leads to a doubling of the complication rate. (19,20) The majority of women who elect CPM elect immediate breast reconstruction. (21) Immediate breast reconstruction is associated with higher rates of complications and reoperation (22,23) compared to mastectomy without reconstruction.…”
Section: Introductionmentioning
confidence: 99%